Pengaruh Penerapan Media Pembelajaran Berbasis Teknologi yang Tepat Terhadap Keterlibatan Aktif Siswa Selama Pembelajaran Daring - Dejan Filgod; Wiyun Philipus Tangkin (Peneliti.net, 2022)
Online learning uses information and communication technology as a medium. Online learning is being implemented to fulfill students' educational rights during the covid-19 pandemic. Some problems occurred throughout its implementation, such as the lack of students' involvement in the classroom. They become less focused on learning, so they do not pay attention to the instructions well. The task processing becomes disrupted to the extent students passed the submission time and even did not submit. Also, students do not communicate problems or obstacles they face to the teacher. Based on several studies, students are less involved in class due to many assignments and difficulties in understanding the teacher's material. Therefore, this paper aims to describe the impact of the implementation of technology-based learning media on students' active involvement in class. Learning media must be adapted to students' psychological condition, which is disturbed during online learning. The used media can combine both kinds of interaction, such as synchronously and asynchronously. Besides, the media must be practical or easy to use for students. Proper implementation of technology-based learning media is expected to assist students in actively involved in the class. Therefore, it is recommended that all parties involved, especially teachers, use media suitable for students' conditions during online learning. Exploration must also be carried out to obtain more useful learning media sources.